2008
DOI: 10.1071/mf07095
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton community relationship to environmental variables in three Kenyan Rift Valley saline-alkaline lakes

Abstract: Temporal changes in total alkalinity, ionic composition and nutrient concentrations were studied in the saline, alkaline endorheic Kenyan Rift Valley Lakes Bogoria, Nakuru and Elmentaita to understand the association of these variables with phytoplankton community structure. In total, 24 taxa were found, with L. Bogoria having the fewest species. Although the cyanobacterium Arthrospira fusiformis dominated the phytoplankton biomass, especially in L. Bogoria, other groups came into play especially during high w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 41 publications
2
51
1
Order By: Relevance
“…However, the maximum abundance of that PPP community was two orders of magnitude smaller than the values presented here ). Other saline lakes at various locations around the globe can similarly be favourable habitats for photoautotrophic picoplankton blooms (Fanjing et al 2009;Wu et al 2009;Krienitz et al 2012), although some lakes have been found to be dominated also by other taxa above the pico size range (García et al 1997;Harper et al 2003;Schagerl and Oduor 2008). In several East African soda lakes picoeukaryote abundances can exceed 3 million cells ml -1 (Krienitz et al 2012),…”
Section: Picoeukaryote Abundance and Primary Productionmentioning
confidence: 99%
“…However, the maximum abundance of that PPP community was two orders of magnitude smaller than the values presented here ). Other saline lakes at various locations around the globe can similarly be favourable habitats for photoautotrophic picoplankton blooms (Fanjing et al 2009;Wu et al 2009;Krienitz et al 2012), although some lakes have been found to be dominated also by other taxa above the pico size range (García et al 1997;Harper et al 2003;Schagerl and Oduor 2008). In several East African soda lakes picoeukaryote abundances can exceed 3 million cells ml -1 (Krienitz et al 2012),…”
Section: Picoeukaryote Abundance and Primary Productionmentioning
confidence: 99%
“…This highly sought after food resource has been observed to undergo significant changes in its biomass over time. Ballot et al (2004) observed changing dominance between A. fusiformis (hereinafter referred to as, Arthrospira) and Anabaenopsis abijatae Kebede & Willén in some saline lakes, which have been attributed to their response to the changing environmental stress expressed as fluctuations in physical and chemical variables (Schagerl & Oduor, 2008). Since Lesser Flamingos are specialised consumers of Arthrospira, such changes in biomass and quality are bound to affect the population of these birds in these soda lakes and in some cases, may also contribute to the sporadic mass mortalities observed at times.…”
Section: Introductionmentioning
confidence: 99%
“…KrieniTz et al 2003;BalloT et al 2005;Schagerl & oDuor 2008;KrieniTz & KoTuT 2010;Kaggwa et al 2012), where temporal trends have often indicated periodic dominance and absence of certain taxa especially at extreme salinity. Apart from the predominant Arthrospira, also other cyanobacteria occur in these lakes.…”
Section: Introductionmentioning
confidence: 99%